Sistema de control de bienes del grupo propiedad, planta y equipo del fondo ecuatoriano Populorum Progressio Regional Guaranda, al año 2017 - Vásquez Soria, Luis Andrés (2018)
The work started from the ill-advised practice of control maintained by the Fondo Ecuatoriano Populorum Progressio Regional - Guaranda. For this, strategies of predecessor studies that support the research process a scientific sustenance to the variables were established. Through a bibliographic, descriptive and field investigation, a diagnosis was made about the current situation and immersed factors of the object of study. Also, techniques and instruments were applied such as the survey, interview, and observation directed to all the staff of the Regional-Guaranda. All this information obtained was processed in the Microsoft Excel computer program, which allowed me to determine qualitatively and quantitatively the percentages for each one of the questions representing, through tables and statistical graphs, the data resulting from the process. After this processing I was able to present conclusions that, in summary, demonstrated the need to improve control of the assets owned by the foundation, in terms of the recommendation proposes the design of a control system for asset assets, plant and equipment, in which policies, norms, forms and procedures are proposed that would improve the administrative management of the Regional-Guaranda. Keywords: Control, Properties, Plant and Equipment, Administrative Management